Determination of optimal implantation site in central venous system for wireless hemodynamic monitoring. (April 2020) - Manavi, Tejaswini; Vazquez, Patricia; Tubassam, Muhammad; Zafar, Junaid; Sharif, Faisal; Zafar, Haroon
Abstract: Background/purpose: In recent years, treatment of heart failure patients has proved to benefit from implantation of pressure sensors in the pulmonary artery. Despite this, pulmonary artery pressure is related to the left ventricle, and cannot provide information on the right side of the heart. By contrast, pressure in the central venous system is directly connected to the right atrium and could potentially predict a wider range of heart failure conditions. The purpose of this work is to find an optimal site for implantation in the central venous system of a hemodynamic wireless sensor for heart failure monitoring. Since all previous hemodynamic sensors were located in the pulmonary artery, there is no existing information about an optimal site in the central venous system. Methods: This study analysed data obtained from CT scans of most relevant anatomical features in the inferior vena cava. The most important parameters of the sites of interest were extracted, analysed statistically and compared, with the purpose to select an optimal site of implantation. Results: The results obtained show that the area comprised between the iliac bifurcation and the lower renal vein (and between the second and third lumbar veins) is the most suitable site of implantation for a hemodynamic sensor. Parameters such as its straight anatomy, diameter (21 mm) and link distance (106 mm) present it as a convenient location for implantation. Its procedure appears relatively easy, as access from the femoral vein is close to the site of interest. In addition, there are not major delicate structure in its surroundings that may pose a risk to the patient. Conclusion: This study concludes that the area between the iliac join and the lower renal vein (and the 2nd and 3rd lumbar veins) is an optimal site for the accommodation of a hemodynamic sensor.